Language and peace on WhatsApp and Facebook messages on the Anglophone crisis in Cameroon - Nouhou, PENIEL ZAAZRA (International Journal of Linguistics and Translation Studies, 2022)
This study set out to explore the promotion of peace by some social media messages related to the ongoing crisis in Southern Cameroons. Focus is on the lexical choice and style that show ways out of the warped communication out of language crisis, and the possible impacts of the messages on the readers’ minds of Cameroonians and other world citizens. The theory of Critical Discourse Analysis (CDA) by Fairclough (1989, 1992, 1995a, 1995b) guided the analysis of the data (150 messages) collected from 75 participants (45 males and 30 females) both from WhatsApp (100) and Facebook (50) posted by Cameroonians from the English-speaking part. The researcher and the field assistants used the Android phone to collect these data. Results reveal that there is an intensive war of words and words of war almost every line of the e-messages from either of the platforms. The numerous messages of peace are overshadowed and outnumbered by verbal bullying and the tense mood in the discourses. Some messages advocate national unity and push readers to think of peaceful co-existence. Therefore, readers are served with messages that feed them with bitterness about the current affairs in the country and accept war for peace to reign; in other words, the messages of peace are likely to recruit less militants than the words call for uprising. Key words: Peace, WhatsApp and Facebook messages, CDA, Anglophone crisis, ideology